Idiopathic Sclerosing Orbital Inflammation in a Relapsing Polychondritis Patient With Impaired Vision. Issue 6 (September 2019) - Wang, Chrong-Reen; Hsu, Sheng-Min; Chen, Ying-Chen; Ho, Chung-Liang; Fang, Sheen-Yie
Abstract : Abstract: A 55-year-old woman with relapsing polychondritis had progressively enlarged right retro-orbital tumor invading the optic nerve, followed by left retrobulbar infiltrating lesions despite prescription of high-dose corticosteroids and pulse methylprednisolone. Repeated histopathologic analyses showed dense collagen fibers with scanty inflammatory cells, consistent with the diagnosis of idiopathic sclerosing orbital inflammation. This disorder has been recognized as a distinct entity with unique clinical features and coexisting rheumatologic disorders, requiring more focused diagnostic strategies and therapeutic regimens. In summary, we demonstrate a rare ocular manifestation in relapsing polychondritis and emphasize the importance of serial radiological and pathological evaluations in such patients presenting with exophthalmos.